Hypertension; East and West - Abdul Rahman, Abdul Rashid; Abdul Rashid, Aneesa (MedCrave Group, 2017)
Hypertension is the number one public health burden accounting for most cardiovascular morbidity and mortality worldwide. While the more developed western countries have shown some success in combating hypertension, the same cannot be said for developing and newly developed countries in the East. The prevalence of hypertension is increasing in the East and coupled with low awareness, and poor blood pressure control on treatment, it will continue to pose substantial health demand in the East. Lessons needs to be learned from the West to combat this public health scourge.